COMPUTER NETWORK MANAGEMENT AND ADMINISTRATION INTERNATIONAL TRADE AND UNPARALLELED TECHNOLOGICAL INNOVATIONS (International Journal of Food and Nutritional Sciences, 2023)
The paper concludes that Computer network management has catalyzed the need to accelerate public sector reforms in developing countries and the need to set up correctly-working institutions. The current Computer network management and administration movement reveals unprecedented levels of exchange felled by levels of consumer demand never previously known, carrying a potential for growth and prosperity transcending any that the world had ever recorded. Computer Network Management and Administration refers to the subject of managing 'computer networks'. Network Management and Administration Services helps company system administrator to manage a network. Wide variety of software and hardware products are existing in IT industry.